Lack of polymorphism of the agouti signaling protein (ASIP) gene among four different brown hare (Lepus europaeus Pallas 1778) populations - Soós, Noémi; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
The brown hare (Lepus europaeus Pallas 1778) is a common palearctic and a popular game species therefore it has been an obvious subject for population genetic studies since the second part of the 20th century. Among the several mitochondrial DNA studies some have been carried out concerning nuclear genes as well. The agouti signaling protein gene (ASIP) is involved in regulating the synthesis of eumelanin and pheomelanin in melanocytes of mammals. Though many studies focused on it in relation with several mammalian species, minimal information is available on this topic concerning the brown hare. Here we present a short communication concerning the agouti signaling protein (ASIP) gene in four different country’s L. europaeus populations, namely Lithuania, Hungary, Serbia and Georgia. N=45 tissue samples have been investigated from overall 17 sampling sites of the different countries. There has not been found any polymorphism among the sequences. In an alignment with other Leporid species’ partial ASIP sequences downloaded from ENA we have found that based on a 178 base pairs long DNA sequence the haplotype of our samples contains three other Lepus species as well. This is concordant with the findings of a previous study focusing predominantly on the European rabbit (Orycto lagus cuniculus Linnaeus 1758) and the several mutations of its ASIP gene.